FAKTOR-FAKTOR YANG MEMENGARUHI UNMET NEED KB DI PROVINSI BENGKULU TAHUN 2015 DENGAN PEMODELAN REGRESI LOGISTIK BINER - Abyan Rai; Reza Rizky Ramadhan (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2018)
Indonesia failed to reach the target to reduce the percentage of unmet need KB in 2015. Province of Bengkulu which has almost 20% of family planning services from government, has a high unmet need percentage. The purpose of this research is to determine the factors that affect status of unmet need KB of women aged 15-49 years in Bengkulu 2015. Data in this study obtained from Susenas 2015. The result showed that 21,34% of women aged 15-49 years in Bengkulu in 2015 was unmet need KB and 78,65% was not unmet need KB. Using binary logistic regression, the result showed that the age of women, number of surviving children, education of women aged 15-49 years, and type of residence have a significant effect on status of unmet need KB. Socialization of family planning program on Bengkulu is needed to reduce the percentage of unmet need KB of women aged 15-49 years on Bengkulu. Further research is suggested to use other independent variables and see spatial correlation in Province of Bengkulu.